DIRECT ERROR CORRECTION ON STUDENTS WORK: ITS EFFECT TOWARDS STUDENTS ABILITY IN WRITING NARRATIVE PARAGRAPH - Helena Badu (Jurnal Inovasi, 2010)
This research aimed to find out whether the direct error correction effect students ability in writing narrative paragraph. This research is useful the english students in order to improve their ability in writing paragraph. The instrument in collecting the data is taken from students writing. They participated in the current research by writing narrative paragraphs. I found that direct error correction can effect significantly students ability in writing narrative paragraphs.